Treinamento técnico em laboratório de análises microbiológicas de alimentos - Sousa, Leonardo Hummel de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Acreddited by the Federal Council of Biology, the biologists can work in the food industry related to the production, research, development, and quality of food (CFBio, 2019). Related to food microbiology area, it is governed by law that food of any kind must undergo a quality analysis, in order to know the degree of microbiological contamination. In Brazil, there are regulations that specifically provide for the subject, requiring the commitment of industries and laboratories to ensure that the final consumer has food that doesn’t pose a risk to his health. Based on a series of rules and standards, the food microbiology laboratory needs daily monitoring so that everything happens in a zealous way, requiring good communication, attention to detail and time management. At this context, a training internship was carried out in a private food microbiology laboratory, where theoretical contents studied in the undergraduate and professional development course were worked on. The internship worked on laboratory maintenance, checking equipment, and the environment, preparing the culture medium and handling common and infectious waste.

Reconhecida pelo Conselho Federal de Biologia, o biólogo pode trabalhar na indústria de alimentos relacionados com a produção, pesquisa, desenvolvimento e qualidade de alimentos (CFBio, 2019). Relacionado à área de microbiologia de alimentos, é regido por lei que alimentos de qualquer natureza devem passar por uma análise de qualidade, com o objetivo de saber o grau de contaminação microbiológica deste. No Brasil, existem normatizações que dispõem especificamente sobre o assunto, exigindo comprometimento de indústrias e laboratórios para assegurarem que o consumidor final tenha um alimento que não ofereça riscos à saúde dele. A partir de uma série de normas e padronizações, o laboratório de microbiologia de alimentos necessita de acompanhamento diário para que tudo ocorra de forma zelosa, necessitando de boa comunicação, atenção aos detalhes e boa gestão de tempo. Diante do presente contexto, foi realizado um estágio de treinamento em um laboratório de microbiologia de alimentos particular, onde foram trabalhados conteúdos teóricos vistos no curso de graduação e aprimoramento profissional na área em questão. O estágio tratou sobre a manutenção do laboratório, checagem de equipamentos e ambiente, preparo de meio de cultura e manejo de resíduos comum e infectante.
Technical training in the laboratory of microbiological analysis of food
Keywords: Food microbiology; Microbiology laboratory; Food; Maintenance; Culture medium; Waste; Microbiologia de alimentos; Laboratório de microbiologia; Alimentos; Manutenção; Meio de cultura; Resíduos